Psychometric instrument development of the sustainable balanced scorecard for the success of a new product development - Aminaimu, Zhengxiaoming; Fernando, Yudi (Inderscience Enterprises Ltd., 2021)
In the past, the BSC is known as a performance measurement system based on advanced cost accounting techniques like how it was first formed. Yet, limited evidence in the literature explains how the BSC perspective is used for new product development and how to measure it. This paper aims to develop psychometric instruments of sustainable BSC for the success of a new product development. A dataset was collected from a survey of production managers who had past experiences in direct handling of new product developments. This study found that patterns of correlations have emerged in internal and external domains of a manifest variable of BSC. We have proposed an extended model of sustainable BSC for new product development. Although the success of new products on the market depends on many factors, our results suggest that BSC is a useful strategic technique to design and develop success of a new product.